An investigation of Chinese university EFL learner’s foreign language reading anxiety, reading strategy use and reading comprehension performance - Lu, Zhongshe; Liu, Meihua (Studies in Second Language Learning and Teaching, 2015)
The present study explored the interrelations between foreign language (FL) reading anxiety, FL reading strategy use and their interactive effect on FL reading comprehension performance at the tertiary level in China. Analyses of the survey data collected from 1702 university students yielded the following results: (a) Both Foreign Language Reading Anxiety Scale (FLRAS) and Foreign Language Reading Strategy Use Scale (FLRSUS) had important subcomponents, (b) more than half of the students generally did not feel anxious when reading English, and were confident in and satisfied with their English reading proficiency. Meanwhile, (c) more than half of them moderately used different types of reading strategies such as planning, checking and confirming, predicting and assessing, when reading English, (d) compared with their female peers, male students felt significantly more anxious when facing reading activities, less satisfied with their English reading proficiency, and used specific analyzing and planning strategies significantly less often during a reading activity, (e) FLRAS was significantly inversely related to FLRSUS, and both were significantly correlated with the students’ FL reading comprehension performance, and (f) FLRAS (overall FL reading anxiety), FLRAS1 (general anxiety about FL reading), and FLRSUS2 (predicting strategies) were good predictors of FL reading comprehension performance. Based on the findings, some implications are discussed.